Rancang Bangun Modul Percobaan Seven Segment Dan Shift Register Di Laboratorium Elektronika Dan Digital Fakultas Teknik Universitas Mataram - Sya'rani, Ilvina; Darmawan, Budi; Ch, Syafaruddin (JEITECH (JOURNAL OF ELECTRICAL ENGINEERING, INFORMATION TECHNOLOGY, CONTROL ENGINEERING, AND ROBOTIC), 2024)
Design of the seven segment and shift register experimental module. The aim of designing this tool is to make it easier for Electrical Engineering students at Mataram University to retrieve data during practicum. Previously, students needed a long time to collect data, 20-30 minutes, after the existence of this tool, students only needed 10-15 minutes to collec data. In the data seven-segment experiment, the output displayed a seven segment display, while in the shift register experiment the output is shown by an LED indicator, including several subs such as the right shift register, left shift register, and circular shift register. This design uses IC MC14495, 7476, 7432, 7404 and 7408 equipped with several other components... so that output results are obtained that match the input provided.